Performance Optimization - Hasim Hasibuan, Ibrahim; Farida Ferine, Kiki (Proceedings of the International Conference on Multidisciplinary Science (INTISARI), 2024)
Human resources are a very strategic and fundamental factor in an organization. Compared to other factors, human resources are the most valuable asset. The role of human resources will greatly determine the success or failure of the organization in achieving the vision and mission that has been set, therefore human resources are very important for the organization. Apart from determining success, the position of human resources in organizations today is not only as a means of production but also as a driver and determinant of the ongoing activities of the organization. The results of this research are as follows: Job Satisfaction has a positive and significant effect on Performance with original sample values of 0.246 and p values 0.000. Job Satisfaction has a positive and significant effect on Role Conflict with an original sample value of 0.545 and ap value of 0.000. Teamwork has a positive and significant effect on Performance with an original sample value of 0.268 and ap value of 0.004. Teamwork has a positive and significant effect on Role Conflict with an original sample value of 0.560 and ap value of 0.002. Role Conflict has a positive and significant effect on Performance with an original sample value of 0.446 and ap value of 0.000. Role Conflict has a positive and significant effect on Performance with an original sample value of 0.446 and ap value of 0.000. Job Satisfaction has a positive and significant effect on Performance through Role Conflict indirectly with an original sample value of 0.243 and ap value of 0.002. Teamwork has a positive and significant effect on performance through role conflict indirectly with an original sample value of 0.161 and ap value of 0.007.